Role of hydrogen peroxide in the neutrophil-mediated release of prostacyclin from cultured endothelial cells. - Harlan, J M (1984)
We have examined the effect of activated neutrophils on the release of prostacyclin (PGI2) from cultured endothelial cells by radioimmunoassay and thin layer chromatography of its stable metabolite, 6-keto-prostaglandin F1 alpha (6-keto-PGF1 alpha). Phorbol myristate acetate-activated neutrophils induced a time- and dose-dependent release of 6-keto-PGF1 alpha from human and bovine endothelial cell monolayers, whereas phorbol myristate acetate alone and neutrophils alone did not. Pretreatment of the endothelial cells with aspirin prevented neutrophil-mediated 6-keto-PGF1 alpha release, indicating that it did not depend upon neutrophil-generated endoperoxides. Phorbol myristate acetate-activated neutrophils from a patient with chronic granulomatous disease failed to induce endothelial 6-keto-PGF1 alpha release. Addition of catalase but not of superoxide dismutase significantly reduced human and bovine endothelial 6-keto-PGF1 alpha release by phorbol myristate acetate-activated neutrophils. Catalase-inhibitable endothelial 6-keto-PGF1 alpha release was also observed after the addition of the hydrogen peroxide-generating system, glucose-glucose oxidase, to bovine and human endothelial cell monolayers. Bovine endothelial 6-keto-PGF1 alpha release induced by exogenously generated hydrogen peroxide was attenuated by the phospholipase inhibitor mepacrine, suggesting that hydrogen peroxide may act by triggering endothelial membrane phospholipase activation. The release of 6-keto-PGF1 alpha by enzymatically or neutrophil-generated hydrogen peroxide was not associated with endothelial cell lysis as assessed by 51Cr release. We conclude that exogenously generated hydrogen peroxide or a hydrogen peroxide-derived product mediates rapid nonlytic release of PGI2 from cultured endothelial cells.